Social networks and HIV treatment adherence among people with HIV initiating treatment in rural Uganda and peri-urban South Africa - Comfort, Alison B; Asiimwe, Stephen; Amaniyre, Gideon; Orrell, Catherine; Moody, James; Musinguzi, Nicholas; Bwana, Mwebesa Bosco; Bangsberg, David R;; Haberer, Jessica E; Tsai, Alexander C (Elsevier, 2024)
Timely initiation of and adherence to antiretroviral therapy (ART) is critical for improving HIV outcomes and reducing HIV transmissibility. Social networks, or the social relationships individuals have with each other, have been linked with positive health outcomes, but less is known about the extent to which social network composition and structure are associated with improved ART adherence among people living with HIV (PLWH). We conducted an ego-centric network study among 828 previously ART-naïve PLWH presenting for ART initiation at 11 clinics in Mbarara, Uganda (rural population) and Gugulethu, South Africa (peri-urban population). We collected social network data using name generator and name interpreter questions. ART adherence was monitored over 12 months using wireless monitors (Wisepill). Our primary outcome of interest was ART adherence during the 12-month follow-up period. We used generalized linear models to estimate the associations between network measures and ART adherence. PLWH at the Uganda site (compared with the South Africa site) were less isolated, had larger social networks, and had more social ties providing sufficient social support; they were also more likely to bridge different social groups whereby not all social ties were connected to each other. In Uganda, social isolation was associated with a 5.5 percentage point reduction in ART adherence (95% confidence interval [CI] -9.95 to -1.13; p = 0.014), while having more same gender social ties was associated with higher ART adherence (b = 0.13, 95% CI 0.02-0.25, p = 0.025). In South Africa, there was no association between social isolation and ART adherence, and having more friendship ties (vs. family ties) was associated with lower ART adherence (b = -2.20, 95% CI -3.56 to -0.84; p = 0.002). Identifying and supporting PLWH who are isolated may facilitate optimal adherence, but understanding how networks differentially affect ART adherence by country context is important.
Keywords: Social networks; HIV/AIDS; Uganda; South Africa; Antiretroviral therapy; Adherence